Revisão bibliográfica da manutenção preditiva e seus conceitos de tecnologia atrelados a Indústria 4.0 - Santos Neto, Manoel Ferreira (2018)
The present study intends to present industry innovation studies 4.0 focused on maintenance phases in the factory, with the main focus being the bridge to the predictive maintenance, in this way, studying how one behaves in relation to the other. Maintenance will be considered as an essential means for the advent of the "New Industrial Revolution", and its impacts on automation and risk prevention. Showing how the industry expects and will react to the advent of interconnected and automated systems across the industry, thereby facilitating control of the entire production chain, and greater visibility into cyberspace-based processes, increased data security, and robot autonomy.